2018
DOI: 10.1177/0198742918808484
|View full text |Cite
|
Sign up to set email alerts
|

Cover-Copy-Compare for Multiplication With Students With Emotional and Behavioral Disorders: A Brief Report

Abstract: A multiple-baseline across participants design was used to investigate the effect of the Cover-Copy-Compare (CCC) intervention on multiplication-fact fluency for students with emotional and behavioral disorders (EBD). Although CCC is a well-researched intervention for mathematics, limited research has been conducted with students with EBD even though these students often struggle academically. Results indicate that a functional relation was established between CCC and an improved number of digits correct per m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…CCC is a self-managed instructional strategy developed by McGuigan (1975) and C. L. Hansen (1978) to help students improve their spelling and has been used successfully since the mid-1970s to improve students' performance with a variety of other content, including math facts (e.g., Becker et al, 2009;Grafman & Cates, 2010;Poncy et al, 2007;Schrauben & Dean, 2019;Skinner et al, 1991). Researchers have also demonstrated that CCC can be used to improve math fact fluency specifically for students with EBD (e.g., Schrauben & Dean, 2019;Skinner et al, 1993). The effectiveness of CCC may be explained using the learning principles of contiguity, contingency, recency, and frequency (Skinner et al, 1993).…”
Section: Cover-copy-comparementioning
confidence: 99%
“…CCC is a self-managed instructional strategy developed by McGuigan (1975) and C. L. Hansen (1978) to help students improve their spelling and has been used successfully since the mid-1970s to improve students' performance with a variety of other content, including math facts (e.g., Becker et al, 2009;Grafman & Cates, 2010;Poncy et al, 2007;Schrauben & Dean, 2019;Skinner et al, 1991). Researchers have also demonstrated that CCC can be used to improve math fact fluency specifically for students with EBD (e.g., Schrauben & Dean, 2019;Skinner et al, 1993). The effectiveness of CCC may be explained using the learning principles of contiguity, contingency, recency, and frequency (Skinner et al, 1993).…”
Section: Cover-copy-comparementioning
confidence: 99%
“…"Mental health difficulties with primary indicators involving inner emotions as opposed to outer conduct" is how emotional problems are described (Sondhi, 2007, p. 34). As opposed to inner feelings and emotions, the definition of behavioral difficulties is mental health problems with principal indicators involving outer behaviors (Schrauben & Dean, 2019). Emotional problems can be defined when as mental health issues with primary indications involving inner emotions as in opposition to the outward behavior (Thackery & Harris, 2003).…”
Section: Emotional and Behavioral Problemsmentioning
confidence: 99%
“…One example of an SI approach mentioned in the Popham et al (2018) review is Cover-Copy-Compare (CCC). CCC is a cognitive strategy effective in helping students, including those with EBD, self-regulate their own learning while engaging in academic tasks (Cook & Cook, 2013;Konrad & Joseph, 2013;Schrauben & Dean, 2019). The CCC strategy includes modeling, high rates of correct responding, practice, and corrective feedback, and it is used to teach both academic and self-management skills.…”
Section: Sm Of Attention (Luanne)mentioning
confidence: 99%